The Tales of Uncle Remus : The Adventures of Brer Rabbit - Lester, Julius; Pinkney, Jerry (New York : Dial Books, 1987)
A retelling of the Afro-American tales about the adventures and misadventures of Brer Rabbit and his friends and enemies.
Keywords: Afro-Americans -- Folklore; Tales -- United States; Folklore, Afro-American; Animals -- Fiction; Folklore -- United States